Study of iodine adsorption in the dynamic mode for several carbon adsorbents - Sokolenko, V.I.; Levenets, V.V.; Vinokurov, E.I.; Grigorova, T.K.; Lonin, A.Yu.; Omelnik, A.P.; Sibileva, R.M.; Shchur, A.A. (Вопросы атомной науки и техники, 2015)
The absorption efficiency of iodine vapor in the dynamic mode for number carbon adsorbents from different manufacturers was studied. In the experiments we have used a stand which was created in NSC simulating the adsorber of NPP ventilation system. The amount of adsorbed iodine was determined by X-ray radiometric and nuclear physics (ANPC "SOKOL") methods. The offered technique will be used for the optimal choice of new adsorbents for carbon filters of NPP ventilation systems. Проведено дослідження ефективності поглинання пари йоду в динамічному режимі для деяких вуглецевих адсорбентів різних виробників. У експериментах використовувався створений в ННЦ ХФТІ стенд, що моделює роботу адсорбера АУ-1500 системи вентиляції АЕС. Кількість адсорбованого йоду визначалася рентгенорадіометричним і ядерно-фізичним (АЯФК "СОКІЛ") методами. Запропонована методика буде використана для оптимального вибору нових адсорбентів для вугільних фільтрів систем вентиляції АЕС. Проведено исследование эффективности поглощения паров йода в динамическом режиме для ряда углеродных адсорбентов различных производителей. В экспериментах использовался созданный в ННЦ ХФТИ стенд, моделирующий работу адсорбера АУ-1500 системы вентиляции АЭС. Количество адсорбированного йода определялось рентгенорадиометрическим и ядерно-физическим (АЯФК «СОКОЛ») методами. Предложенная методика будет использована для оптимального выбора новых адсорбентов для угольных фильтров систем вентиляции АЭС.